2013
DOI: 10.3233/jae-131722
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric coupling model for asphalt mixtures based on microwave heating

Abstract: In order to improve recycling quality of asphalt mixtures based on microwave heating, thermoelectric coupling theory is researched. Heat conduction equation is built according to Fourier's Law. Series model, parallel model and Maxwell model are studied to solve thermal conductivity of asphalt mixtures. Radiation field model of pyramidal horn antenna is set up and mean value of electric field intensity is measured by experiment. Thermoelectric coupling model is built on the basis of dielectric property of aspha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Research describing in uence on basaltic and siliceous-calcareous aggregates showed their susceptibility to microwave heating with slightly higher in uence on basalt (Benedetto and Calvi, 2013). On the basis of other studies, there was no effect of the increasing temperature of the aggregate by microwave radiation, e. g. quartzites and limestones (Sun, 2013;Trigos et al, 2020b), while heating of the bitumen containing polar fractions was observed (Norambuena-Contreras and Garcia, 2016). It is worth mentioning that the lower microwave frequency was used the greater penetration of heated materials was observed (Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Research describing in uence on basaltic and siliceous-calcareous aggregates showed their susceptibility to microwave heating with slightly higher in uence on basalt (Benedetto and Calvi, 2013). On the basis of other studies, there was no effect of the increasing temperature of the aggregate by microwave radiation, e. g. quartzites and limestones (Sun, 2013;Trigos et al, 2020b), while heating of the bitumen containing polar fractions was observed (Norambuena-Contreras and Garcia, 2016). It is worth mentioning that the lower microwave frequency was used the greater penetration of heated materials was observed (Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…According to some sources, aggregates are a material susceptible to polarization and microwave heating (Trigos et al, 2020a), also dependent on the moisture content of the material and the aggregate origin (Al-Ohaly and Terrel, 1988). Some studies mark that only some aggregates are susceptible to the microwave in uence (Gulisano and Gallego, 2021) and among them we can point out andesite, ophite, blast furnace slag (Trigos et al, 2020b) and diorite (Sun, 2013). Research describing in uence on basaltic and siliceous-calcareous aggregates showed their susceptibility to microwave heating with slightly higher in uence on basalt (Benedetto and Calvi, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Compared with other heating methods (i.e., hot air, flame, infrared, electric coils, and hydronics), the microwave heating (MH) technique is considered as an innovative maintenance solution due to its rapid, uniform, non-polluting, and deep penetrating heating characteristics [ 3 , 4 , 5 ]. Microwaves are a form of electromagnetic waves in the frequency range of 300 MHz to 300 GHz [ 6 ], which generate a volumetric heating phenomenon [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The D-dot probe can sample transient voltage through electric field coupling to realize non-contact installation [14][15][16][17][18][19]. A difference input structure is presented to make the D-dot probe work in a selfintegrating mode.…”
Section: Introductionmentioning
confidence: 99%